Macrophage activation syndrome in a patient with systemic lupus erythematosus undergoing cyclophosphamide treatment: a case report - L. Fioravante da Silveira; A. Zago; D. Zanchet; D. Chemello (PAGEPress Publications, 2023)
Macrophage activation syndrome (MAS) is a disorder related to hemophagocytic lymphohistiocytosis and is a life-threatening complication of rheumatic diseases. The diagnosis is challenging because MAS symptoms are quite similar to those of many active autoimmune diseases or severe sepsis. We describe the case of a female patient with systemic lupus erythematosus that presented with symptoms suggesting acute decompensation of autoimmune disease and sepsis. She was later diagnosed with MAS. Despite an aggressive immunosuppressive treatment, she developed a fatal outcome.